Biblical Principles of Hiring and Developing Employees - Winston, Bruce E. (Christian Faith Perspectives in Leadership and Business, 2018)
This book begins with the scriptural support for person-organization fit and person-job fit. The book then examines scriptural support for the four-Cs of people's work-fit: Calling, Competence, Confidence, and Character. Finally, the book uses Acts 6:1-7 as a basis for identifying the type of people one should look to hire. The book covers two development concepts: Nomos, about ruling in an organization, and progressive responsibility from Luke 16:10. The chapters present the concepts from a scriptural base and include composite case examples that relate to contemporary organizations. .